Measuring Brain Haemodynamic Activity and Afferent Visual Function: A Preliminary Study on the Relationship Between fNIRS, the King–Devick Test and Suspected Sport-Related Concussions - Mark Hecimovich; Terence Moriarty; Doug King; Tricia Majewski-Schrage; Kate Hermsen (Physiologia)
Background/Objectives: Functional near-infrared spectroscopy (fNIRS) may help quantify changes in brain haemodynamics during sport-related concussions (SRCs). This study compared post-match prefrontal cortex (PFC) brain haemodynamics measured by fNIRS during the King–-Devick test (K-DT) with players suspected of having sustained an SRC. It was hypothesized that changes in the K-DT would correspond with brain haemodynamic processes. Methods: Twenty-two male and female collegiate rugby players (six males and twenty-two females; age range: 18–22) completed a baseline K-DT+fNIRS assessment. Over the course of two to three matches, all participants were invited to complete at least one post-match K-DT+fNIRS assessment. If a player was suspected of having sustained an SRC, they were re-assessed with the K-DT+fNIRS. If a participant who was not suspected of having sustained an SRC performed worse on the K-DT post-match, they were included in the participant category of ‘concussion’ for the analysis. A repeated measures ANOVA was performed. Test–retest reliability was calculated using the intra-class correlation coefficient (ICC). A Pearson correlation coefficient (r) assessed the linear relationship between the changes in the K-DT and the measurements of the left and right PFC. Results: Differences were identified in the K-DT for the players with a suspected concussive injury post-match (χ2(1) =5.0; p = 0.0253; z = −2.0; p = 0.0431; d = 0.16). There were also significant differences between the baseline and post-match results for all concussed players in the right PFC (t(8) = 250; p = 0.0371; d = 0.92) and for the concussed females in the right PFC (t(6) = 2.78; p = 0.0319; d = 0.52). There were no correlations between the K-DT and PFC values in the suspected concussed group. Conclusions: The SRC group had decreased cognitive performance and a notable change in PFC activation, while the non-concussed group showed an increase in the activation in the PFC and no change in cognitive performance scores. This represents a possible acute adjustment in brain haemodynamics and provides insight into how SRCs can negatively impact cognitive performance.